Arte Indígena Contemporânea Decolonialidade e ReAntropofagia: Contemporary Indian Art Decoloniality and Reanthropogagy - Luna, Gloria Alejandra Guarnizo; Flores, Maria Bernardete Ramos; Melo, Sabrina Fernandes (Farol, 2022)
The article reflects on the decolonial dimension of contemporary indigenous art, through the tactic of (re)anthropophagy and insurgency, through the approach to the production of indigenous artists, who mix cosmological references and indigenous visualities with appropriations of Western artistic canons, languages ​​and technologies. Artists, who occupy institutionalized spaces and enter the contemporary art market, promoting fissures in the hegemonic narratives about the original peoples of Brazil. This phenomenon, which appears in the Brazilian contemporary art scene, will be perceived in dialogue with the thoughts, actions and poetics of two indigenous artists, recognized in Brazil and abroad. Jaider Esbell, who brings the foundations of what is configured as Art Contemporary Indigenous, and Denilson Baniwa, who conceived the Puçanga Art and its power to insurrect, bewitch and heal colonial wounds.